Kebijakan Tarif Poligami ( Studi Atas Peraturan Bupati Lombok Timur Nomor 26 Tahun 2014 Tentang Pelaksanaan Peraturaan Daerah Nomor 3 Tahun 2013 Tentang Lain-Lain Pendapatan Asli Daerah Yang Sah) - Sahuddin Sahuddin (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2015)
This study discusses polygamy rate policy set by the Regent of East Lombok asone revenue. It is known that Republk Unitary State of Indonesia based on Pancasilaand the Constitution of 1945, both of which are the basis of the highest in the stateconstitution Indonesia. After the reform in 1998, was born the Law No. 22 of 1999and Law No. 32 Year 2004 on Regional Government. This Act gives effect to theregions in Indonesia. So there is a new law called local regulations (Perda). The presenceof the executive branch and the legislature named regent named DPRD. The localgovernment tried to create legislation that is based on Pancasila and the 1945Constitution which considers the potential and regional interests necessarily. After doingresearch, we concluded that the East Lombok decree No. 26 of 2014 on theImplementation of Regional Regulation No. 3 of 2013 in accordance with the purposeof siyasah jurisprudence. Because the East Lombok Regent Regulation contains thevalues the benefit of society and the prevention of damage which are elements in thesiyasah jurisprudence. The regulation protects against women who do not want topolygamy